1990
DOI: 10.1152/ajpregu.1990.259.4.r792
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex responses to acute changes in blood volume in humans

Abstract: To test the hypothesis that acute changes in plasma volume affect the stimulus-response relations of high- and low-pressure baroreflexes, eight men (27-44 yr old) underwent measurements for carotid-cardiac and cardiopulmonary baroreflex responses under the following three volemic conditions: hypovolemic, normovolemic, and hypervolemic. The stimulus-response relation of the carotid-cardiac response curve was generated using a neck cuff device, which delivered pressure changes between +40 and -65 mmHg in continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
32
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 0 publications
8
32
2
Order By: Relevance
“…That is, the MSNA response for a given change in CVP was as expected. The repeatability of MSNA burst frequency on different days (9,47,50) provides confidence in this conclusion.…”
Section: Discussionsupporting
confidence: 57%
“…That is, the MSNA response for a given change in CVP was as expected. The repeatability of MSNA burst frequency on different days (9,47,50) provides confidence in this conclusion.…”
Section: Discussionsupporting
confidence: 57%
“…Data during bed rest suggested that cardiopulmonary baroreflex-related effects are blunted and that blood pressure maintenance in the presence of an orthostatic stimulus relies mostly on arterial control. arterial blood pressure; variability; baroreflex; lower body negative pressure; bed rest MILD OR NONHYPOTENSIVE LOWER body negative pressure (LBNP; Ϫ20 mmHg Ͻ LBNP Ͻ 0 mmHg) has been used to selectively unload cardiopulmonary baroreceptors (25,44,46,50). However, straightforward observations of the time course of mean arterial pressure (MAP) following rapid onset of mild LBNP (17, 18) evidenced a transient decrease followed by a recovery of pre-LBNP onset values, suggesting that arterial baroreceptors are affected by mild LBNP as well.…”
mentioning
confidence: 99%
“…MILD OR NONHYPOTENSIVE LOWER body negative pressure (LBNP; Ϫ20 mmHg Ͻ LBNP Ͻ 0 mmHg) has been used to selectively unload cardiopulmonary baroreceptors (25,44,46,50). However, straightforward observations of the time course of mean arterial pressure (MAP) following rapid onset of mild LBNP (17,18) evidenced a transient decrease followed by a recovery of pre-LBNP onset values, suggesting that arterial baroreceptors are affected by mild LBNP as well.…”
mentioning
confidence: 99%
“…Orthostatic stress can be induced nonpharmacologically by upright posture, or simulated using lower body negative pressure (LBNP). Many studies illustrate an increase in the groupaveraged forearm and leg vascular resistance during these tests (29,164,253,283) that are sensitive to norepinephrine (NE) release (253). In humans, head-up tilt elicits predictable increases in sympathetic outflow and total vascular resistance, the magnitude of which expresses interindividual variability (105).…”
Section: Baroreflexmentioning
confidence: 99%